CODE-SWITCHING BETWEEN INDONESIAN AND ENGLISH ON A TELEVISION TALK SHOW - M. Asmi Rizaldy; Muhamad Khoerul Hadist (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
This study looked into Sarah Sechan's use of Indonesian-English code-switching on the private-run Net TV talk show host. The study looked at the different kinds of code-switching, its purposes, and the social encouragement provided by code-switching that took place during the conversation. After obtaining the data from the downloaded videos, the theories of Poplack (1980), Gumperz (1982), and Myers-Scotton (1998) were used to analyze the data. The discoveries uncovered that the three sorts of code-switching, the intra-sentential code-switching, the between sentential code-switching and the extra-sentential code-switching existed. The intra-sentential code-switching, which is thought to be the more complex of the three, was used the most frequently in verbal communication. Quote marking, addressee specification, interjections, reiteration, message qualification, personalization versus objectivization, topic switch, affective function, expressive, phatic, metalinguist, and directive were also identified as twelve functions of code-switching. Predominant was the reiteration function. In the meantime, the social triggers of code-switching were identified as the sequence unmarked choice maxim and the deference choice maxim.